Effects of Phosphorus Fertilizer Levels on Growth, Yield and Economic Efficiency of Groundnut Under Semi-Arid Regions of Afghanistan - Khalilullah Khaleeq; Najibullah Hemmat; Mohibullah Samim; Muhammad Atiq Ashraf (PT FORMOSA CENDEKIA GLOBAL, 2023)
A field experiment was laid out at the Afghanistan National Agricultural Science and Technology University (ANASTU) Farm in cropping season of 2020 to investigate optimization of phosphorus doses on growth, yield and economic efficiency of groundnut in semi-arid region of Afghanistan, the experiment laid out in Randomized Complete Block Design (RCBD) with three replication, the treatments consist of 5 phosphorus doses viz. absolute control, 20, 40, 60 and 80 kg p2o/ha, the result of the investigation revealed the highest plant height ( 34.42 cm), Branches/plant (10.88), leave area (2260 cm2), pods/plant (40.25), Kernel/pod (2.97), pod yield (3.39 t/ha), haulm yield (6.11 t/ha) and Biological yield (9.50 t/ha) were in phosphorus application at the rate of 60 kg p2o/ha. From the result it should be concluded by the applying optimum level of phosphorus fertilizer groundnut production will increase up to 3.39 t/ha, the farmers should apply phosphorus application at the rate of 60 kg p2o5/ha for enhancing groundnut productivity and profitability